Different phenotypes of severe flares in patients with systemic lupus erythematosus: results of a clustering analysis in a monocentric cohort - Elefante, E.; Schilirò, D.; Manca, M. L.; Stagnaro, C.; Zucchi, D.; Cardelli, C.; Signorini, V.; Maffi, M.; Cascarano, G.; Zas, R.; Carli, L.; Ferro, F.; et al. (Frontiers in Immunology, 2025)
ObjectivesTo describe different clinical phenotypes of severe flares in a monocentric cohort of SLE patients and to compare treatment and outcomes.Material and methodsRetrospective study of prospectively collected data on 122 severe flares occurred in 110 patients, between 2018 and 2023, and followed up for 12 months after the flare. Baseline characteristics included disease activity assessment by SELENA-SLEDAI and BILAG 2004 scores, demographic and laboratory data. A hierarchical unsupervised segmentation method was applied to cluster flares based on baseline features. Treatments and outcomes according to LLDAS, DORIS Remission and SRI definitions, were compared among clusters at different timepoints.ResultsWe identified 3 clusters, 2 composed mainly by extra-renal, and one by renal flares. Among non-renal clusters, cluster 1 was characterized by severe constitutional symptoms, serositis and arthritis occurring in younger patients, associated with hyper-inflammatory biomarkers and multiple autoantibodies specificities. Cluster 2 included flares with more BILAG B scores and mainly mucocutaneous and musculoskeletal manifestations, and overlapping antiphospholipid syndrome (APS). Cluster 3 was the renal flares cluster. Cluster 1 and the renal cluster were treated more frequently with glucocorticoid (GC) pulses and mycophenolate mofetil (MMF) and presented higher daily and cumulative GCs doses at 12 months (t12). These two clusters also shared similar percentage of attainment of LLDAS (about 50%) and remission (about 35% both) at t12, compared to 73% of LLDAS and 53% of remission in cluster 2 at t12.ConclusionsWe described three different clusters of severe flares in SLE in a real-life setting, identifying a hyper-inflammatory flare phenotype, that shares a comparable proportion of unsatisfying response to treatment as renal flares. Our results may represent a clinical starting point, in the context of precision medicine, for better characterization of severe non-renal disease of SLE, with the final aim of setting up early tailored treatment strategies.